2002
DOI: 10.1046/j.1439-0442.2002.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Keratan Sulphate as a Cartilage Metabolic Marker in Horses: the Effect of Exercise

Abstract: Keratan sulphate (KS) concentration in sera from resting horses and horses training daily on a racetrack was measured by an inhibition enzyme-linked immunosorbent assay (ELISA) using anti-equine KS antibody 1/14/16H9. For the in-training horses, serum KS concentrations in 2-year-old-horses was significantly higher than 3- or 4-year-old-horses. A higher concentration of serum KS was found in the in-training group than in the long-term resting group in 2-year-old-horses. Serum KS concentration increased remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Another study reported a decrease in aggrecan synthesis and concomitant increase in decorin synthesis in equine cartilage explants that persisted for 16 wks of rest following 17 wks of strenuous exercise [ 97 ]. Increases in CS and keratin sulfate (catabolic marker of cartilage metabolism) have been associated with cases of osteochondral fragmentation in horses [ 24 ] and repetitive exercise over time [ 22 , 98 ]. Healthy horses seem to be able to return to homeostatic conditions in joint tissues fairly quickly as was the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a decrease in aggrecan synthesis and concomitant increase in decorin synthesis in equine cartilage explants that persisted for 16 wks of rest following 17 wks of strenuous exercise [ 97 ]. Increases in CS and keratin sulfate (catabolic marker of cartilage metabolism) have been associated with cases of osteochondral fragmentation in horses [ 24 ] and repetitive exercise over time [ 22 , 98 ]. Healthy horses seem to be able to return to homeostatic conditions in joint tissues fairly quickly as was the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Changes suggestive of microdamage and weakening of the type II collagen network of articular cartilage have been reported in strenuously exercised young racehorses 20 , whereas moderate exercise has been shown to have a beneficial effect on glycosaminoglycan (GAG) content of articular cartilage in young 21 and adult 22 horses. It has been reported that the serum and synovial fluid levels of keratan sulfate, a GAG found on the individual proteoglycan molecules of aggrecan, are increased in young horses and ponies as a result of exercise 13,23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for the fact that synovial GAG levels were not elevated in joints with moderate-severe cartilage damage could be that GAG released into SF is subsequently cleared from the joint very rapidly and levels therefore do not accumulate to values greater than in normal joints. Glycosaminoglycans are released into SF and then pass via lymph vessels into the bloodstream (Worrall et al 1994;Okumura et al 2002) and they have been shown to leave the joint within a few hours (Antonas et al 1973). This process has been shown to occur even more rapidly in inflamed joints (Myers et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that factors other than joint disease influence the amount of GAG in SF. Exercise has been shown to have such an effect, with serum keratan sulphate (KS) being elevated shortly post exercise (Okumura et al 2002). On the other hand, exercise has been shown to decrease GAG release from cartilage (van den Hoogen et al 1998).…”
Section: Discussionmentioning
confidence: 99%